Application of Artificial Freezing Method in Deformation Control of Subway Tunnel - Jie Li; Jinke Li; Yuancheng Cai; Dingyi Wu; Chunxia Guo; Wencai Zhao; Kunjie Tang; Yuhang Liu (Advances in Materials Science and Engineering)
The metro tunnel construction mainly passes through the downtown area, including ground buildings, infrastructure, underground pipelines, existing subway lines, and station floors. However, it is very difficult to control the ground deformation, especially in the water-rich soft ground or in the tunnel engineering construction with strict requirements for surface settlement control. The traditional stratum reinforcement method may not meet the engineering needs. In this case, the artificial freezing method (AFM) provides a solution for such engineering problems. This paper summarizes the basic principle and characteristics and application scope of AFM, and compared with the other three stratum reinforcement methods, AFM has better effect in controlling surface displacement and vault settlement, while grouting method, pipe shed method, and pipe curtain method have absolute advantages in controlling surface uplift. Then, through engineering examples, the reinforcement effect of AFM in the four aspects of subway connecting passage, shield inlet and outlet, interval tunnel, and damage repair is introduced. Through analysis, it is found that the reinforcement effect of AFM in water-rich weak stratum is very good. Finally, the future development of AFM is prospected in order to provide some experience and guidance for the follow-up research.